Partial orders and fully abstract models for concurrency - Engberg, Uffe (DAIMI Report Series, 1990)
In this thesis sets of labelled partial orders are employed as fundamental mathematical entities for modelling nondeterministic and concurrent processes thereby obtaining so-called noninterleaving semantics. Based on different closures of sets of labelled partial orders, simple algebraic languages are given denotational models fully abstract w.r.t. corresponding behaviourally motivated equivalences. Some of the equivalences are accompanied by adequate logics and sound axiomatisations of which one is complete.